'Staying True to Theatrical Life': Bicycle Theatre Group in Northern Sri Lanka - Thevananth, Thevanayagam (Indian Journal of Tamil, 2022)
During the war in the northern part of Sri Lanka, theatre committees functioned on a monthly allowance basis. This activity has been going on continuously for many years. These theatre groups have travelled relying on people. The people have fed them. Here the salary allowance was not paid according to the quality of the actor in the theatre group, but according to the number of his family members. Instead of 'qualified wages', the allowance of 'wages as per requirement' has been given. A group of equal numbers of women and men have cycled and staged plays. The play has been staged in at least three places every day, travelling day and night continuously for 22 days in a month. The actors, who went on bicycles professionally and staged plays, performed real life on stage. They saw the reality of the stage in life. There are no differences between fiction and reality in this theatre journey. The real story becomes a drama. A drama story becomes a reality. Here the dramaturgy fits in with many true stories and becomes visions of realities. At the same time, after a play is over, more plays are created. Moreover, more and more have evolved. Here, the play has helped the affected people reach the stage of 'despair'. It leads to a state of repentance, collective empathy, gaining confidence, and a desire to live. This study is based on the stage definition of liberation, on the basis of the ethnographic point of view, on the basis of which the researcher himself lived at a given time, and on the basis of witnessing the plays. But there are gaps in this study. To further enrich the study, the fonts of the plays produced by the theatre groups recorded sound, and cinematography is also required. Observation studies are also required. They are limited in the context of a military crisis.